Skip to content

russellgoyder/geometric-algebra-cheat-sheet

Folders and files

NameName
Last commit message
Last commit date

Latest commit

 

History

34 Commits
 
 
 
 
 
 
 
 
 
 
 
 

Repository files navigation

{% include head.html %}

Geometric Product

Identity Comment
$ab = a \cdot b + a \wedge b$ Geometric product of two vectors $a$ and $b$
$a \cdot b = \frac{1}{2}\left( ab + ba\right)$ Inner product of two vectors as symmetric part of geometric product
$a \wedge b = \frac{1}{2}\left( ab - ba\right)$ Exterior product of two vectors as antisymmetric part of geometric product

Multivectors

Identity Comment
$a_1 \wedge\dots\wedge a_r = \frac{1}{r!} \sum_{\mathcal{K}} (-1)^\epsilon a_{k_1} \dots a_{k_r}$ Exterior product of $r$ vectors. $\mathcal{K}$ is the set of permutations of $1 \dots r$ and $\epsilon$ is even for even perms and odd for odd
$a_1 \wedge a_2 \wedge a_3 = \frac{1}{6} \left( a_1a_2a_3+a_3a_1a_2+a_2a_3a_1-a_1a_3a_2-a_2a_1a_3-a_3a_2a_1\right)$ Example of the above for $r=3$. Note $a \wedge b = \frac{1}{2}\left( ab - ba\right)$ is example for $r=2$
$a \cdot A_r = a A_r - (-1)^rA_r a \qquad (*)$ Prove by repeated application of $ab = 2a\cdot b - ba$ to $a a_1\dots a_r$ for orthogonal ${a_i}$
$a \wedge A_r = a A_r + (-1)^rA_r a \qquad (**)$ Extends definition of $\wedge$ to multivectors
$aA_r = a\cdot A_r + a\wedge A_r$ Combine above two formulae. $a\cdot A_r$ has grade $r-1$, $a\wedge A_r$ has grade $r+1$
$A_r\cdot(B_s\cdot C_t) = (A_r\wedge B_s)\cdot C_t \quad r+s\leq t \qquad (\triangleleft)$ Prove by grade projection
$A_r\cdot(B_s\cdot C_t) = (A_r\cdot B_s)\cdot C_t \quad r+t\leq s \qquad (\triangleright)$ Ditto
$a\cdot (a_1 \wedge\dots\wedge a_r) = \sum_{k=1}^r (-1)^{k+1} a\cdot a_k ; a_1 \wedge\dots\wedge \check a_k \wedge\dots\wedge a_r$ The check on $\check a_k$ means "omit that term from the exterior product"

Vectors and Bivectors

Identity Comment
$a\cdot(b\wedge c) = a\cdot b;c - a\cdot c;b$ Simplest example of above identity, $r=2$
$a\cdot(a_1\wedge a_2\wedge a_3) = a\cdot a_1;a_2\wedge a_3 - a\cdot a_2;a_1\wedge a_3 + a\cdot a_3;a_1\wedge a_2$ Next simplest example, $r=3$
$(a\wedge b)\cdot B = a\cdot (b\cdot B)$ Application of $(\triangleleft)$ in the case $r=s=1$ and $t=2$
$(a\cdot B) \cdot b = a\cdot(B\cdot b)$ Application of $(\triangleright)$ in the case $r=t=1$ and $s=2$
$(a\wedge b)\cdot(c\wedge d) = b\cdot c; a\cdot d - a\cdot c ; b\cdot d$ Expand into geometric products and use $ab = 2a\cdot b - ba$
$a\cdot(b\wedge B) = a\cdot b; B - b\wedge(a\cdot B)$ Expand into geometic products using $(*)$ and $(**)$

Commutator Product

Identity Comment
$M \times N = \frac{1}{2}(MN-NM)$ Definition, for multivectors $M$ and $N$
$L\times(M\times N) + N\times(L\times M) + M\times(N\times L) = 0$ Jacobi identity for multivectors $L$, $M$ and $N$
$B\times a = \frac{1}{2}(Ba-aB) = B \cdot a$ Special case for bivector $B$ and vector $a$ using $(*)$
$B\times A_r = \langle B\times A_r\rangle_r$ Commutator product with bivector is grade-preserving for blade $A_r$ and hence multivector $M$
$BA_r = B\cdot A_r + B\times A_r + B\wedge A_r$ Therefore $\frac{1}{2}(BA_r + A_rB) = B\cdot A_r + B\wedge A_r$
$(a\wedge b)\times B = (a\cdot B)\wedge b + a\wedge (b\cdot B)$ Expand into geometic products using $(**)$ and def'n of commutator product

Pseudoscalar

Identity Comment
$I = e_1 \wedge\dots\wedge e_n$ For orthonormal vectors ${e_i | i=1\dots n}$
$I^2 = \pm1$ Sign depends on metric but is typically -1 in physics applications
$IA_r = (-1)^r(n-1)A_rI$ For blade $A_r$ in $n$-dims. $I$ always commutes with even-grade multivectors
$a\cdot (A_rI) = a\wedge A_r, I$ Using the above commutation rule together with $(*)$

Linear Algebra

Identity Comment
$b = \mathsf F(a) $ Linear function (whose components form a matrix)
$\mathsf F(\mu a + \nu b) = \mu\mathsf F(a) + \nu\mathsf F(b)$ Linearity for vectors $a$ and $b$ and scalars $\mu$ and $\nu$
$\mathsf F(a\wedge b)=\mathsf F(a) \wedge \mathsf F(b)$ Action on a bivector
$\mathsf F(\mu M + \nu N) = \mu \mathsf F(M) + \nu \mathsf F(N) \ \mathsf F(A_r) = \langle\mathsf F(A_r)\rangle_r$ Linearity and grade-preservation for multivectors $M$ and $N$, and blade $A_r$
$a\cdot\overline{\mathsf F}(b) = \mathsf F(a)\cdot b$ Definition of $\overline{\mathsf F}$, the adjoint (transpose) of $\mathsf F$
$\langle A,\overline{\mathsf F}(B)\rangle = \langle\mathsf F(A) , B \rangle \qquad (\bullet)$ Multivector version of above definition of adjoint
$A_r\cdot \overline{\mathsf F}(B_s) = \overline{\mathsf F}\left(\mathsf F(A_r)\cdot B_s\right) \qquad r\leq s \qquad $ Combine definition of adjoint with $(*)$, eg for $A_r = a$ and $B_s = b\wedge c$
$\mathsf F(A_r)\cdot B_s = \overline{\mathsf F}\left(A_r\cdot \overline{\mathsf F}(B_s)\right) \qquad r\geq s \qquad (\dagger)$ Combine definition of adjoint with $(*)$, eg for $A_r = a\wedge b$ and $B_s = c$
$R = nm = \exp(-\hat B\theta/2) = \cos(\theta/2) - \hat B\sin(\theta/2)$ Rotor $R$ from vectors $m$ and $n$ where $m\cdot n = \cos\theta$, $\hat B = \frac{m\wedge n}{\sin(\theta/2)}$ and $\hat B^2 = -1$
$\mathsf F(M) = RM\tilde R$ Multivector $M$ rotated by angle $\theta$ in $\hat B$ plane

Determinant and inverse

Identity Comment
$\mathsf F(I) = \det(\mathsf F), I$ Definition of determinant, as volume scale factor for $\mathsf F$
$\det(\mathsf F\mathsf G),I = \det(\mathsf F)\det(\mathsf G), I$ Because $\det(\mathsf F\mathsf G),I = \mathsf F\mathsf G(I) = \det(\mathsf G), \mathsf F(I) = \det(\mathsf F)\det(\mathsf G), I$ using the above definition
$\det(\mathsf F) = \det(\overline{\mathsf F})$ Because $\det(\mathsf F) = \langle\mathsf F(I)I^{-1}\rangle = \langle I\overline{\mathsf F}(I^{-1})\rangle = \langle \overline{\mathsf F}(I^{-1})I\rangle = \det(\overline{\mathsf F})$ using $(\bullet)$
$\mathsf F^{-1}(M) = \frac{1}{\det(\mathsf F)} I \overline{\mathsf F}(I^{-1}M)$ Inverse of $\mathsf F$. Holds also when $\mathsf F \rightarrow \overline{\mathsf F}$. From definition of determinant, multiply by arbitrary multivector $N$: $$\det(\mathsf F)IN = \mathsf F(I)N = \mathsf F\left(I\overline{\mathsf F}(N)\right)$$ using $(\dagger)$ and that $\mathsf F(I)\cdot N = \mathsf F(I)N$ and $I\cdot \overline{\mathsf F}(N) = I\overline{\mathsf F}(N)$. Now let $M = IN$ and apply $\mathsf F^{-1}$ to both sides.

CC BY 4.0

This work is licensed under a Creative Commons Attribution 4.0 International License.

CC BY 4.0

About

Identities and key results in Geometric Algebra that are useful to me and hopefully others

Resources

License

Stars

Watchers

Forks

Languages